A Rare Case Report on Madura Foot - Bysani, Vasavi; Pabbathi, Asha Latha; Gopineni, Divya (Indian Journal of Pharmacy Practice)
Mycetoma is a chronic infectious disease of the subcutaneous tissue. It is new designated by World Health Organization (WH0) which is endemic in tropical and subtropical regions.1 Mycetoma can be caused by a large variety of microorganisms. The infection caused by tramautic inoculation of a (Eumycetoma) Fungi or a (Actinomycetoma) bacterium.2 It is a disorder of subcutaneous tissue, skin and bones, mainly of feet, characterized by a traid of localized swelling underlying sinus tracts and production of granules.3 Treatment of disease depends on the etiology of the causative agent.2 Since the treatment of two etiologies is entirely different, A definite diagnosis after histopathological and microbiological examination is necessary, Serological test exists but is not so reliable.3 The treatment has been surgical debridment or amputation. Noninvasive management with long term antimicrobials has been successfully reported.
Keywords: Actinomycetoma; Madurafoot; Mycetoma; Nocardia; Dapsone.